Chitosan-based hydrogels: Physicochemical properties and mechanical behavior - Silva, Rafael Leonardo Cruz Gomes da (2025)
This thesis focused on the study of chitosan hydrogels and their composite systems, aiming to develop models with potential biomedical applications. Chapter 1 introduces general aspects of chitosan, including its structure, sources, physicochemical properties, crosslinking processes, and applications. In Chapter 2, curcumin was incorporated into chitosan hydrogels crosslinked with different vanillin contents, using SDS, Tween 20®, and β-cyclodextrin as encapsulating agents. The best incorporation results (~3.0 mg/g) were obtained with films containing 20% vanillin and SDS. These systems proved to be non-cytotoxic and promising for curcumin release under acidic erosion conditions. Chapter 3 presents studies on the incorporation of PDMS dispersions to modulate the Young’s modulus of chitosan and vanillin-crosslinked chitosan hydrogels, targeting the development of cell scaffolds. Hydrogels with elastic moduli ranging from 60 to 600 kPa were produced, and good adhesion of myoblasts as model cells was observed. In Chapter 4, the impact of hydration state and aqueous phase dynamics on the mechanical properties of chitosan hydrogels was evaluated through uniaxial tensile testing and AFM nanoindentation. Both methods showed good agreement in the measured Youngs modulus values. Moreover, it was observed that both the hydration state and the presence (or absence) of swelling equilibrium with the aqueous medium directly influence the calculated elasticity values. Chapter 5 presents preliminary results on the interactions between chitosan and casein under different pH values and concentrations, in solution, aiming the formation of composite hydrogels for cell scaffold applications.